DIGITAL ASSETS AS PART OF HERITAGE OBJECTS: AN APPROACH TO INDONESIAN POSITIVE LAW AND CONTEMPORARY FIQH MAWARIS - Zulkarnaini Umar,; Miftakhul Mukharrom, (Proceeding International Conference on Social Sciences, 2026)
echnological developments and technological advancements are unavoidable for modern humans today. For example, technology has given rise to various forms of digital assets with economic value and legally valid ownership. This situation raises new questions regarding the status of digital assets as objects of inheritance under Indonesian positive law and contemporary Mawaris fiqh. This study aims to analyze the legal status of digital assets as inheritance property from the perspective of Indonesian positive law and contemporary Mawaris fiqh. This research was conducted using normative research methods with a juridicalcomparative approach. The results indicate that pluralism in inheritance law in Indonesia has not fully addressed the complexity of inheritance issues in the form of digital assets. This has the potential to create legal uncertainty and trigger conflict between heirs. However, contemporary Mawaris fiqh views digital assets as al-amwal al-mutaqawwimah (inheritance) that must be inherited by heirs as long as they fulfill the elements of benefit and value. Therefore, legal reform that is responsive to the development of digital technology is needed, both through specific regulations for digital assets and strengthening more adaptive inheritance mechanisms.